A cross-cultural study of environmental concern and attitudes among German, Dutch and Turkish publics - Ermin, Sevil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1993., 1993)
The main purpose of the present study is to provide a framework related to the level of environmental concern. attitudes. and perceptions of Turkish, Dutch and German consumers. Examined subjects are awareness of the the consumers in the three countries about global and national environmental problems and level of importance of these problems; perceptions of environmentally friendliness and environmentally friendly products and companies as well as the perceived roles of related parties; actual participation level and willingness to contribute to the environmental solutions; perceived causes and solutions of problems; most common sources of environmental information. willingness to pay extra or taxes for an environmentally friendly product; and the impact of environmental friendliness on purchaSing behaviour. After a thorough review of the relevant literature on the subject of 'environment' is made. an empirical research has been conducted on the passengers of the Germany and Holland flights of a Turkish private airline company. A structured and an undisguised questionnaire has been given to a sample of 294 respondents by non-probabilistic judgemental sampling method through which the data for the study has been collected. Data are entered to Excel 4.0 and frequency analyses are made through this program and cross-tab analyses are made with SPSSPC. The major finding of the study is that a great percentage of Turkish, Dutch and German populations exhibit a high level of concern for the environmental problems of the 'world particularly. At national level, economic and social problems precede environmental ones, especially for the Turkish respondents. Dutch and Germans engage in recycling and careful disposal activities mostly, whereas the Turks mostly perform activities related to saving energy or other resources. Producers are perceived to be the major responsible party for environmental pollution; they and government are expected to work for the improvement of environmental quality. Implications upon the major findings of the study are discussed referring to four parties related to the subject; ie. producers, governments, consumers, and the researchers. Major contribution of the study has been to the literature, because of its generic function by offering data, background information and research scope. Another important contribution has been providing implications to the related individuals and organisations.
Keywords: Green marketing.; Product management -- Environmental aspects -- Cross-cultural studies.